SEEDLINGS OF CARDAMOM (Elettaria cardamomum (L.) Maton) EVALUATION BY RESISTANCE in vitro AT CULTURE FILTRATES OF Fusarium oxysporum Link - ZÚÑIGA S., Dorcas; HOYOS S., Rodrigo; AFANADOR K., Lucía (Vitae, 2010)
Fusarium oxysporum Link is the cause of basal rotting in cardamom. The present article evaluates the phytotoxical effect of of the fungus crude filtrate,for selecting somaclonal variations of cardamom that showed resistance in greenhouse pathogenicity tests. According to mortality test results clone 5 and the isolated 4 were pointed with the most susceptibility-virulence interaction. From accelerated growth media seedlings there were selected 25 and inoculated with different concentrations of filtrate, causing mortality on the initial weeks. By the sixth week only a 32% resisted the concentration increment. By the tenth cycle of inoculation 100% of seedlings remained in the crude filtrate without dilutions. The more time the seedlings remain in accelerated growth media and the more selection pressure increasing filtrate concentration show increased probability of getting somaclonal variants with in vitro resistance of Fusarium oxysporum.